Wing cell shape variation in malaria vector species of the Anopheles barbirostris complex and closely related species (Diptera: Culicidae) - SEDTHAPONG LAOJUN; ARINA ABDULLOH; ATIPORN SAEUNG; TANAWAT CHAIPHONGPACHARA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Laojun S, Abdulloh A, Saeung A, Chaiphongpachara T. 2025. Wing cell shape variation in malaria vector species of the Anopheles barbirostris complex and closely related species (Diptera: Culicidae). Biodiversitas 26: 3711-3721.  Several Anopheles species, including members of the An. barbirostris complex, contribute significantly to malaria transmission in Thailand. Accurate species identification is hindered by high morphological similarity, reducing the effectiveness of traditional taxonomy. This study examined wing cell shape variation in three complex members (An. dissidens, An. saeungae, An. wejchoochotei) and their sister species An. hodgkini using an outline-based geometric morphometric approach. A total of 136 specimens—An. dissidens (n = 30), An. saeungae (n = 30), An. wejchoochotei (n = 46), and An. hodgkini (n = 30)—were analyzed. Eleven wing cells were digitized, and shape variables extracted via Elliptic Fourier Analysis were evaluated with discriminant analysis to assess interspecific variation. Significant shape differences (p < 0.05) were detected for most species pairs and wing cells. Anopheles hodgkini exhibited the greatest morphological divergence, especially in the first basal, marginal, and second posterior cells. In contrast, some comparisons within the complex, such as between An. dissidens and An. wejchoochotei in the anal cell, were not significant (p > 0.05). Cross-validated reclassification accuracy ranged from 44.12% (anal cell) to 58.09% (second posterior cell). These results demonstrate that wing cell shape analysis can support discrimination among morphologically similar malaria vectors. Geometric morphometrics offers a cost-effective, rapid method for assessing morphological variation, providing valuable taxonomic resolution and aiding detection of cryptic Anopheles species. While GM alone may not achieve high classification accuracy, it generates complementary morphological evidence to molecular diagnostics. In resource-limited public health settings, GM can serve as a preliminary identification tool, enhancing vector surveillance by enabling more precise mapping of high-risk transmission zones. Accurate differentiation of Anopheles species is essential for effective malaria control, as species vary in vectorial capacity, behavior, and ecology, informing targeted and efficient intervention strategies.